A New Perspective for Assessing Water Transport and Associated Retention Effects in a Large Reservoir. Issue 18 (23rd September 2018) - Xu, Bochao; Yang, Disong; Yao, Peng; Burnett, William C.; Ran, Xiangbin; Charette, Matthew; Huang, Xinying; Liu, Sumei; Yu, Zhigang
Abstract: Radioactive tracer techniques may be useful for assessing water transport and the overall effects of concurrent biogeochemical processes in river‐reservoir systems. In this study, we show that radium isotopes can assess the hydrodynamics and sediment/nutrient retention in the Xiaolangdi Reservoir, the largest impoundment along the Yellow River, China. Activity ratios of 224 Ra/ 226 Ra and 223 Ra/ 226 Ra were used for water mass age calculations in the riverine, transition, and lentic reaches of the reservoir. Water ages were combined with the length scale of three river‐reservoir zones to determine water transport rates of 3.6 ± 1.2, 1.3 ± 0.3, and 0.16 ± 0.14 km/day, respectively. Radium ages were also used to quantify the net retention of sediment and nutrients in different parts of the river‐reservoir system. Suspended sediment was removed at a rate of 1.4 ± 0.6 g/m 3 /day, mainly in the riverine zone. Nutrient dynamics were more complicated, with addition or removal at different rates within the three zones. Plain Language Summary: This paper should be of interest to fluvial aquatic scientists and resource managers. Typically, numerical models have been used to estimate reservoir hydrodynamics, and associated biogeochemical processes are investigated separately. Here for the first time, we explore the validity of using radium isotope tracers to assess water age distributions in the Xiaolangdi Reservoir, the largest impoundment along the Yellow River (China). Radium ages were then used to quantitatively evaluate the net retentions of suspended sediments and nutrients within the reservoir. The technique is easy to conduct at relatively low cost and allows one to assess the overall effect of synchronized biogeochemical processes. Key Points: Ra‐age technique is suitable for hydrodynamic assessments in river‐reservoir systems where model assumptions are met Sediment and nutrient retentions may be quantified using Ra water ages Nutrients are added and/or removed at different rates within three identified zones of the reservoir